2008
DOI: 10.1111/j.1365-263x.2008.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

UK National Clinical Guidelines in Paediatric Dentistry: stainless steel preformed crowns for primary molars

Abstract: This revised Clinical Guideline in Paediatric Dentistry replaces the previously published sixth guideline (Fayle SA. Int J Paediatr Dent 1999; 9: 311-314). The process of guideline production began in 1994, resulting in first publication in 1997. Each guideline has been circulated widely for consultation to all UK consultants in paediatric dentistry, council members of the British Society of Paediatric Dentistry (BSPD), and to people of related specialities recognized to have expertise in the subject. The fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(125 citation statements)
references
References 14 publications
3
106
0
16
Order By: Relevance
“…Despite recommendations for conventional stainless steel crowns (Attari and Roberts, 2006;Kindelan et al, 2008), their use is mainly limited to paediatric specialists, with general dentists considering stainless steel crowns too complex, time-consuming, expensive, and not cosmetically acceptable (Threlfall et al, 2005). The HT, however, makes relatively few demands on the child or the dentist, even compared with the technique-sensitive CR.…”
Section: Discussionmentioning
confidence: 99%
“…Despite recommendations for conventional stainless steel crowns (Attari and Roberts, 2006;Kindelan et al, 2008), their use is mainly limited to paediatric specialists, with general dentists considering stainless steel crowns too complex, time-consuming, expensive, and not cosmetically acceptable (Threlfall et al, 2005). The HT, however, makes relatively few demands on the child or the dentist, even compared with the technique-sensitive CR.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] To some extent, these changes have simply refl ected reducing caries experience among children 5 as well as development of new clinical guidelines and policies for evidence-based practice. [6][7][8] Nonetheless, potential defi ciencies in undergraduate paediatric dentistry experience have been acknowledged, both in the UK and worldwide. 3,4,9 In order to address shortfalls in undergraduate experience, increasing emphasis has been placed on the contribution of outreach training.…”
Section: Introductionmentioning
confidence: 99%
“…The British Society of Paediatric Dentistry clinical guidelines thus currently recommend preformed metal crowns (previously known as stainless steel crowns) as the restoration of choice following vital pulpotomy therapy in primary molars. 1,2 It was therefore reassuring to note that the present study reported a signifi cantly higher success rate for pulpotomised teeth where a stainless steel crown had been placed compared to an amalgam restoration. The clear clinical message here is that a hermetic seal is paramount to a successful outcome following primary molar pulp therapy.…”
Section: Commentmentioning
confidence: 50%